2006
DOI: 10.1016/j.neuron.2005.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Runx1 Determines Nociceptive Sensory Neuron Phenotype and Is Required for Thermal and Neuropathic Pain

Abstract: In mammals, the perception of pain is initiated by the transduction of noxious stimuli through specialized ion channels and receptors expressed by nociceptive sensory neurons. The molecular mechanisms responsible for the specification of distinct sensory modality are, however, largely unknown. We show here that Runx1, a Runt domain transcription factor, is expressed in most nociceptors during embryonic development but in adult mice, becomes restricted to nociceptors marked by expression of the neurotrophin rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
479
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(506 citation statements)
references
References 72 publications
17
479
5
Order By: Relevance
“…Here we confirm this Runx1 expression pattern in human anagen HFs using the anti-Runx1 antibody created in the Thomas Jessell laboratory (Fig. 14A) (10). In addition, we showed that Runx1 was expressed in human telogen HFs in epithelial cells at the base of the bulge and in the secondary hair germ, just as we had previously reported in the mouse (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Here we confirm this Runx1 expression pattern in human anagen HFs using the anti-Runx1 antibody created in the Thomas Jessell laboratory (Fig. 14A) (10). In addition, we showed that Runx1 was expressed in human telogen HFs in epithelial cells at the base of the bulge and in the secondary hair germ, just as we had previously reported in the mouse (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Another study also demonstrated mRNA and functional -opioid receptors in rat pups between P6 and P14 (Takeda et al, 2004). In mouse, the postnatal expression of -receptors in a subset of DRG neurons seems to be regulated by the transcription factor Runx1 (Chen et al, 2006). There are some phylogenetic differences in opioid receptor expression in the spinal cord and DRG across mammalian species.…”
Section: Plasticity and Regulation Of Peripheral Opioid Receptorsmentioning
confidence: 92%
“…Runx1 determines the nociceptive sensory neuron phenotype and is required for thermal and neuropathic pain. 25 Other Runx proteins have been reported to control the axonal projection of proprioceptive DRG neurons. 26 Hypermethylated alive deserts were enriched for SOX gene family (P < 10 ¡51 ) and neurofibromin 1 (NF1) binding sites (P < 10 ¡22 ).…”
Section: Alive and Dead Deserts Differ In Their Binding Site Motifmentioning
confidence: 99%